Refugee Crisis in Southeast Asia: Humanitarianism, Security, and Sovereignty - Nobuto, Yamamoto (Archīum Ateneo, 2019)
Southeast Asia experienced two drastically different refugee crises in the 1970s and the 2010s. After the end of the second Indochinese war in 1975, the massive outflow of refugees from Indochinese countries became an international concern and the United Nations High Commissioner for Refugees (UNHCR) began its humanitarian operation in the region. In the 2010s, the Rohingya refugees—allegedly “stateless” people who fled Myanmar (and Bangladesh)—sought safe shores across Southeast Asia. Despite international refugee protection efforts, these asylum seekers are not always welcome in both destinations and in transit countries which claim to prioritize national security over human rights. This article argues that the different attitudes of the international community toward these refugee crises of the 1970s and the 2010s are derived from the international environment in which international norms function.